Blockchain in vehicular ad hoc networks: applications, challenges and solutions - Akhter, A. F. M. Suaib; Ahmed, Mohiuddin; Anwar, Adnan; Shah, A. F. M. Shahen; Pathan, Al-Sakib Khan; Zengin, Ahmet (INDERSCIENCE ENTERPRISES LTD, 2022)
Blockchain has been adopted in a wide range of application domains to enhance security and privacy. Vehicular ad hoc network (VANET) is an important application domain in today's communication systems where incorporation of blockchain is very timely. Recent literature highlights the prospects of blockchain technology in VANET, however, it is imperative to investigate the effectiveness to ensure viability. In this paper, a thorough investigation is conducted to identify the suitability of blockchain for VANET by identifying and answering key research issues. Unlike other existing surveys, challenges related to blockchain integration, evaluation criteria, privacy preservation, cyber security, etc. are also critically analysed. Future research directions such as 6G and large-scale deployment are also identified which need to be addressed by both VANET and blockchain community. Not only VANET, but also vehicular communication systems (VCSs) and intelligent transportation systems (ITSs) have been considered in this survey.
Keywords: blockchain; cyber; intelligent; security; system; transport; vehicular ad hoc network; VANET; cyber security; COOPERATIVE MAC PROTOCOL; KEY MANAGEMENT; 6G NETWORKS; SCHEME; PRIVACY; AUTHENTICATION; OPTIMIZATION; PERFORMANCE; INTERNET; Computer Science; Telecommunications